2003
DOI: 10.1046/j.1523-1755.2003.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring transport of water across the peritoneal membrane

Abstract: Transport of water across the peritoneum can be measured with remarkable accuracy and when combined with an intraperitoneal volume estimation can be used to determine mass transfer. In conditions of low convection, the relative rate of deuterium appearance and mass transfer compared to other solutes suggests that water diffuses predominantly through the intercellular small pores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…We have shown that these requirements are met when the deuterium abundance in the water vapour to be analysed is less than 1000 ppm and using FA-MS in this regime we have made many measurements on TBW in healthy controls and dialysis patients that demonstrate its validity [5][6][7]. But above about 1000 ppm an increasing fraction of the m/z 75 ions become populated with a single D atom in combination with a single 17 O atom and/or two D atoms (see Figure 1 later), and this added complication must then be taken into account in order to obtain accurate deuterium abundances. In some applications of isotopic dilution, restricted volumes of water are involved and this results in a need for measurements of deuterium abundance in water at several thousand parts per million.…”
Section: Sift-ms and Fa-ms For Measurements Of D Abundance In Water Vmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that these requirements are met when the deuterium abundance in the water vapour to be analysed is less than 1000 ppm and using FA-MS in this regime we have made many measurements on TBW in healthy controls and dialysis patients that demonstrate its validity [5][6][7]. But above about 1000 ppm an increasing fraction of the m/z 75 ions become populated with a single D atom in combination with a single 17 O atom and/or two D atoms (see Figure 1 later), and this added complication must then be taken into account in order to obtain accurate deuterium abundances. In some applications of isotopic dilution, restricted volumes of water are involved and this results in a need for measurements of deuterium abundance in water at several thousand parts per million.…”
Section: Sift-ms and Fa-ms For Measurements Of D Abundance In Water Vmentioning
confidence: 99%
“…This allowed the TBW in human subjects to be determined to a comparable precision and accuracy (but see the important proviso and development described in the next paragraph). Much work in the measurement of TBW has been accomplished in collaboration with our clinical colleagues using FA-MS [5][6][7][15][16][17]. However, this method does have a weakness in that by avoiding the upstream mass filter and directly discharging the helium carrier gas/water vapour mixture (which inevitably contains traces of air), ions like NO + and O 2 + are formed in addition to H 3 O + and its hydrates.…”
Section: Sift-ms and Fa-ms For Measurements Of D Abundance In Water Vmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of peritoneal water transport were explored by combining intraperitoneal volume measurements (13) to determine the net ultrafiltration and reabsorption, with an artificially created deuterated water gradient (HDO), to determine diffusion (14). The different pathways of water transport were investigated by creating conditions of low and high convection through both pore systems (using 1.36 and 3.86% glucose, respectively) and by confining convective flow to the intercellular pores using icodextrin.…”
Section: Methodsmentioning
confidence: 99%